Optimization of Rice Bran Oil Bleaching via Carotenoid Adsorption onto Activated Carbon using Response Surface Methodology (RSM) - Damayanti, Astrilia -; Harianingsih, Harianingsih; Bahlawan, zuhriyan Ash Shiddieqy; Dillah, Shohib Qomad; Dewi, Yasinda Verrel Dinara Shinka; Kristi, Silvia Yolanda; Prasetyo, Ridwan Anung (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2023)
Rice bran oil (RBO) is a by-product of rice processing with a good fatty acid profile and high oxidative stability. This study aims to optimize the bleaching stage of the rice bran oil refining process to determine the minimum levels of carotenoids in RBO by using the Response Surface Methodology (RSM). This research used the Central Composite Design (CCD) experimental design with three variables: bleaching temperature (50, 80, 1100C), bleaching time (20, 40, 60 minutes), and activated carbon concentration (0.4, 0.8, 1.2%). As a result, the model was enhanced to explain the correlation of each variable and the different data variations. This study employed the Derringer method to determine the most optimal variable variation that produces the lowest carotene levels. This study found that the optimal carotene level was 4.87 mg/kg with an activated carbon concentration of 1.18%, temperature of 500C, and time of 53.155 minutes.